1997
DOI: 10.1002/(sici)1099-1069(199711)15:4<209::aid-hon615>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation patterns of disseminated intravascular coagulation in acute promyelocytic leukemia

Abstract: Coagulation patterns of 19 newly-diagnosed acute promyelocytic leukemia (APL) patients with disseminated intravascular coagulation (DIC) at presentation were studied. Seventeen patients had hemorrhagic complications, of which four were fatal. Fatal hemorrhages were related with lower fibrinogen level and lower platelet count. DIC of the APL patients without infection was characterized by low fibrinogen and normal antithrombin III (ATIII) level. Thrombin-ATIII complex level was elevated in all patients examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…322 Measurement of tumor necrosis fac tor alpha (TNFa) has been used as a marker in DIC. 323 Severe DIC, with consumption of platelets and clotting factors and bleeding is rare and is most commonly asso ciated with acute promyelocytic leukemia, 324 acute myeloid leukemia (AML), 325 acute lymphoblastic leuke mia (ALL), 326 and adenocarcinomas. DIC can be exacer bated during chemotherapy, particularly in acute myeloid leukemia, as lysis of the cells leads to further release of procoagulant activity.…”
Section: Clinical Manifestations Of a Hypercoagulable Statementioning
confidence: 99%
“…322 Measurement of tumor necrosis fac tor alpha (TNFa) has been used as a marker in DIC. 323 Severe DIC, with consumption of platelets and clotting factors and bleeding is rare and is most commonly asso ciated with acute promyelocytic leukemia, 324 acute myeloid leukemia (AML), 325 acute lymphoblastic leuke mia (ALL), 326 and adenocarcinomas. DIC can be exacer bated during chemotherapy, particularly in acute myeloid leukemia, as lysis of the cells leads to further release of procoagulant activity.…”
Section: Clinical Manifestations Of a Hypercoagulable Statementioning
confidence: 99%
“…[135][136][137][138][139][140][141][142][143][144] There were 3 posthoc studies on data from randomized controlled trials, 104,117,120 2 case series 111,112 and 47 cohort studies, among which data were collected prospectively in 24 96,97,99,105-110,113,115,116,118,123,126,127 129-131,135,136,140,142,144 and obtained from medical records in 23. 2, 94,95,98,100-103,114,119,121,122,124,125,128,132-134,137-139 141,143 Platelet count only was reported in 40 studies, 2, 94,95,97,98,[100][101][102][103][104][105]107,114,[116][117][118][119][120][121][122][124][125][126][127][128][129][130][131][132][133][134]…”
Section: Resultsmentioning
confidence: 99%
“…98 Among studies rating fair, 10 studies reported associations between platelet counts and bleeding. 94,100,103,106,107,118,119,122 Lower median platelet counts in bleeding versus nonbleeding leukemia patients were reported by Higuchi et al (median: 13 Â 10 9 /L vs. 23 Â 10 9 /L) 103 and Kazianka et al (median: 117 Â 10 9 /L vs. 137 Â 10 9 /L). 106 Two studies reported increased bleeding prevalence with platelet counts 10 Â 10 9 /L versus >10 Â 10 9 /L (Aderka et al's study: 51 vs. 20% 94 ; Fu et al's study: 37 vs. 9% 100 ).…”
Section: Hematological Cancersmentioning
confidence: 86%
“…About 60 to 80% of patients have some clotting disorder at diagnosis. Currently, mortality rates secondary to thrombohemorrhagic events during induction occur in around 5 to 7% of patients eligible for clinical studies (B) 14., 19., 20.…”
Section: How Should Coagulopathies In Acute Promyelocytic Leukemia Bementioning
confidence: 99%